Flux intensity and diurnal variability of soil N2O emissions in a highly fertilized cropping system (Data set and statistical analysis script) - Francis Clar, Jordi; Anex, Robert P (My University, 2019)
Statistical analysis and data set used in the publication of the journal article: 'Measuring frequently during peak soil N2O emissions is more important than choosing the time of day to sample'. Francis Clar, J. and Anex, R. P.: Measuring frequently during peak soil N2O emissions is more important than choosing the time of day to sample.
Keywords: Nitrous Oxide, N2O, soil, flux, time, dataset